Ethiopia - Corrigan, Jim. (Philadelphia : Mason Crest Publishers, 2005)
Explores the geography, history, government, economy, people and cultures of Ethiopia.
Geography -- History -- Government -- Economy -- Culture and people -- Cities and communities -- Calendar of festivals -- Recipes -- Glossary -- Project and report ideas -- Chronology.
Includes bibliographical references and index.
Keywords: Ethiopia